The Islamic Religious Education Teacher Ability Strategy in Facing the Challenges of the Digital Era at MTS Miftahul Huda Rama Gunawan - Narda Ahmad; Mispani Mispani; Jaenulloh Jaenulloh (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
This thesis examines the process of forming an understanding of PAI teacher ability strategies among students through Digital IT at Madrasah Tsanawiyah Miftahul Huda Rama Gunawan Seputih Raman, Central Lampung Regency, Lampung Province. This research aims to determine the strategic abilities of PAI teachers in facing the challenges of the digital era among students. The research method used is qualitative research with in-depth interviews, observation and document analysis as data collection tools. The research results show that PAI teachers have a significant role in forming character in students. Through digital IT teaching which is based on the term digital IT, students are able to understand the values of tolerance, pluralism and peace in Islam. Apart from that, the PAI Teacher Strategy also strengthens students' Islamic identity and provides a deep understanding of Islamic teachings. This research makes an important contribution in the context of Islamic religious education in Indonesia, especially in efforts to form a harmonious and tolerant religious character. The implication of this research is the importance of maintaining and developing PAI Teacher Capability Strategies in Facing the challenges of the IT-centric Digital Era as one of the targets for forming a young generation who have strong abilities and are committed to moderate Islamic values. And also has the quality of understanding all digital IT. Keywords: Challenges of the Digital Era, Islamic Religious Education Teacher